Teaching family medicine residents how to answer clinical questions using QUIPs - Bishop, Lisa; Duggan, Norah; Flynn, Heather (Canadian Medical Education Journal, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: “Questions in Practice” (QUIP) rounds are used to encourage residents to quickly find, evaluate, and incorporate information into clinical practice. It is an opportunity for residents to identify a clinical question, research the answer, present the evidence, and discuss how to apply it to practice. The value of using this method to teach residents has not been evaluated. Methods: A sampling of all first and second-year family medicine residents enrolled in the Memorial University Family Medicine program were invited to participate in the survey. The survey gathered information about the residents’ current experiences with answering clinical questions, their experience during QUIP rounds, and the value of an interdisciplinary approach. Results: The response rate was 91% (42/46). Medical websites (45%) and journal article indexes (34%) were most often used. Through QUIPs, 50% of the students identified new methods to retrieve answers, 80% considered it a useful learning experience, 75% had improved confidence, and clinical knowledge improved in 97%. Conclusions: Residents are familiar with many general sources of medical information, and QUIPs helped improve confidence in their knowledge and ability to answer questions. QUIPs appear to be a useful tool for teaching information resources and how to interpret and apply evidence to clinical situations. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>